2004
DOI: 10.1088/0022-3727/37/19/012
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a gas breakdown process in a laser-plasma experiment

Abstract: This paper is mainly concerned with Nd:YAG laser induced plasmas in air at different pressures. A modelling of the formation of laser plasmas is presented. The preionization phase is described using time differential equations that are solved in the basis of the Crank–Nicolson second order scheme. Moreover, the following dynamic phase, described as a strong shock wave expanding out of the focal volume, is simulated by using a two-dimensional compressible flow calculation code. The evolution of pressure, temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…4, where we assume isothermal conditions in the core plasma, are used to calculate the plasma density decay rates over time when the plasma edge density and shock wave front are coincident and when the plasma size is large enough to obtain reliable density measurements, 600 nsՅ t Յ 2 s. The plasma density decay analysis is performed in this time window only in the core region of the plasma with a radius of r = Ϯ 1 mm, where negligible diffusion and isothermal ͑flat temperature͒ spatial profiles are assumed and indicated in other laser shock wave papers. 5,26 During this time window the measured electron density is n e Ն 10 15 cm −3 , in which the assumption of LTE is valid. 13,21 In the absence of an ionizing source, after the laser is turned off, the plasma decay can be described by the continuity equation 19,27 dn e dt = − D a ٌ 2 n e − v a n e − ␣ r n e 2 − ␤ e n e 3 , ͑11͒…”
Section: F Analysis Of Plasma Density Decaymentioning
confidence: 99%
“…4, where we assume isothermal conditions in the core plasma, are used to calculate the plasma density decay rates over time when the plasma edge density and shock wave front are coincident and when the plasma size is large enough to obtain reliable density measurements, 600 nsՅ t Յ 2 s. The plasma density decay analysis is performed in this time window only in the core region of the plasma with a radius of r = Ϯ 1 mm, where negligible diffusion and isothermal ͑flat temperature͒ spatial profiles are assumed and indicated in other laser shock wave papers. 5,26 During this time window the measured electron density is n e Ն 10 15 cm −3 , in which the assumption of LTE is valid. 13,21 In the absence of an ionizing source, after the laser is turned off, the plasma decay can be described by the continuity equation 19,27 dn e dt = − D a ٌ 2 n e − v a n e − ␣ r n e 2 − ␤ e n e 3 , ͑11͒…”
Section: F Analysis Of Plasma Density Decaymentioning
confidence: 99%
“…Due to its fundamental nature, a large subset of this research has been devoted to studies of breakdown in air. [1][2][3][4] This paper reports experimental results of breakdown in air using sub-breakdown threshold intensity, 193 nm excimer laser radiation. Much of the theoretical basis of laser induced breakdown is based upon earlier work describing microwave breakdown.…”
Section: Introductionmentioning
confidence: 99%
“…This evolution feature is most likely related to the different generation and quenching mechanisms of their corresponding excited states. 42,43) A closer observation indicates that a similar or same temporal evolution profile is presented for each of the spectral lines with the relative humidity increased from 65, via 80, to 90 RH%. The temporal evolution for these characteristic spectral lines in different relative humidity further demonstrates that the influence of humidity on timeresolved emission spectra from air plasma is negligible.…”
Section: Time-resolved Emission Spectra Of Air Plasma For Various Rel...mentioning
confidence: 56%
“…It has been reported that in the laser-induced plasma, both the absorption coefficient due to inverse bremsstrahlung and the ionization rate in the case of photoionization grow with the laser irradiance at moderate levels. 42) The enhanced plasma absorption and growing photoionization promote the growth of ablation rate, which brings about the increase of electron density with respect to the laser irradiance, as shown in Fig. 7(d).…”
Section: Determination Of the Plasma Temperature And Electron Density...mentioning
confidence: 94%